Surface Potential and Threshold Voltage Model of Fully Depleted Narrow Channel SOI MOSFET Using Analytical Solution of 3D Poisson’s Equation - Prashant Mani; Manoj Kumar Pandey (Журнал нано- та електронної фізики)
The present paper is about the modeling of surface potential and threshold voltage of Fully Depleted Silicon on Insulator MOSFET. The surface potential is calculated by solving the 3D Poisson’s equation analytically. The appropriate boundary conditions are used in calculations. The effect of narrow channel width and short channel length for suppression of SCE is analyzed. The narrow channel width effect in the threshold voltage is analyzed for thin film Fully Depleted SOI MOSFET.